Nanocrystalline ZrO2 and Pt-doped ZrO2 catalysts for low-temperature CO oxidation - Amit Singhania; Shipra Mital Gupta (Beilstein Journal of Nanotechnology, 2017)
Zirconia (ZrO2) nanoparticles were synthesized by solution combustion using urea as an organic fuel. Brunauer–Emmett–Teller (BET), X-ray diffraction (XRD), thermal gravimetric analysis (TGA), transmission electron microscopy (TEM), UV–vis and Fourier transform infrared (FTIR) measurements were performed in order to characterize the catalyst. The calculated crystallite size of ZrO2, calculated with the help of the Scherrer equation, was around 30.3 nm. The synthesized ZrO2 was scrutinized regarding its role as catalyst in the oxidation of carbon monoxide (CO). It showed 100% CO conversion at 240 °C, which is the highest conversion rate reported for ZrO2 in literature to date. It is found that through solution combustion, Pt2+ ions replace Zr4+ ions in the ZrO2 lattice and because of this, oxygen vacancies are formed due to charge imbalance and lattice distortion in ZrO2. 1% Pt was doped into ZrO2 and yielded excellent CO oxidation. The working temperature was lowered by 150 °C in comparison to pure ZrO2. Further, it is highly stable for the CO reaction (time-on-stream ≈ 40 h). This is because of a synergic effect between Pt and Zr components, which results in an increase of the oxygen mobility and oxygen vacancies and improves the activity and stability of the catalyst. The effects of gas hourly space velocity (GHSV) and initial CO concentration on the CO oxidation over Pt(1%)-ZrO2 were studied.